2020
DOI: 10.1038/s41598-020-71594-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of extranodal extension in sentinel lymph node positive breast cancer

Abstract: The precise stage of lymph node (LN) metastasis is a strong prognostic factor in breast cancers, and sentinel lymph node (SLN) is the first station of nodal metastasis. A number of patients have extranodal extension (ENE) in SLN, whereas the clinical values of ENE in SLN in breast cancers are still in exploration. The aim of our study was to evaluate the predictive and prognostic values of ENE in SLN in breast cancers, and to investigate the feasibility of ENE to predict non-SLN metastasis, nodal burden, disea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Several factors are predictive of non-sentinel LN metastasis, such as tumor size larger than 2 cm (22)(23)(24), number of LNs with macrometastasis (18,24) and extracapsular node invasion (23)(24)(25)(26)(27), which is a warning sign that should be considered for ALND, even when only one SLN is affected (2,8). But the SEER database lacks this report.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are predictive of non-sentinel LN metastasis, such as tumor size larger than 2 cm (22)(23)(24), number of LNs with macrometastasis (18,24) and extracapsular node invasion (23)(24)(25)(26)(27), which is a warning sign that should be considered for ALND, even when only one SLN is affected (2,8). But the SEER database lacks this report.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, a study showed that a subset of patients with a low burden of SLN had a poor prognosis after simple biopsy. Thus, a more precise evaluation of LNs should be performed in clinical practice in the future (42).…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, this microscopic phenomenon would highly increase the risk of disease spread, ultimately affecting patients' survival outcomes. However, there are no strict criteria for the microscopic diagnosis of ENE [20,21]. The detection of ENE may be influenced by observers, leading to a significant interobserver variability.…”
Section: Discussionmentioning
confidence: 99%